Dried Blood Spot Sampling for Tacrolimus and Mycophenolic Acid in Children: Analytical and Clinical Validation. Issue 4 (August 2017) - Martial, Lisa C.; Hoogtanders, Karin E. J.; Schreuder, Michiel F.; Cornelissen, Elisabeth A.; van der Heijden, Jac; Joore, Manuela A.; Van Maarseveen, Erik M.; Burger, David M.; Croes, Sander; Brüggemann, Roger J. M.; Aarnoutse, Rob E.
Abstract : Background: Tacrolimus and mycophenolic acid (MPA) are the backbone of immunosuppressive therapy after pediatric kidney transplantation. Dosing of these drugs is individualized by therapeutic drug monitoring. Dried blood spot (DBS) sampling may prove beneficial over conventional venous sampling. We aimed to develop and clinically validate a DBS method for tacrolimus and MPA in children. Methods: A joint DBS liquid chromatography-mass spectrometry assay for tacrolimus and MPA was developed. DBS-specific items included the hematocrit effect and influence of spot volume. Subsequently, a clinical validation study among children aged 2–18 years was performed to assess the agreement between observed and DBS-predicted venous concentrations. Agreement of the methods was assessed with Passing–Bablok regression, Bland–Altman plots, and quantification of the DBS predictive performance in terms of bias (median percentage prediction error) and precision (median absolute percentage prediction error), both should be <15%. Results: A total of 40 tacrolimus and 32 MPA samples were available from 28 children. Conversion factors were used to predict venous concentrations from DBS. For tacrolimus, 95% of the individual ratios of predicted and observed concentrations were within a range of 0.74–1.28, with 85% of these ratios between 0.80 and 1.20 (Bland–Altman plots). For MPA, the 95% limits of agreement represented a broader range of 0.49–1.49%, and 72% of individual ratios were between the 0.80 and 1.20 limits. Median percentage prediction error and median absolute percentage prediction error were less than 15% for both drugs. Conclusions: A DBS assay was developed for tacrolimus and MPA. Tacrolimus venous concentrations could be adequately predicted from DBS. DBS analysis of MPA seemed to be a semiquantitative measurement at the most when compared with conventional plasma analysis, considering the high variability between observed and predicted concentrations. Next, home-based DBS sampling of tacrolimus for the purpose of therapeutic drug monitoring will be implemented into routine clinical care. Abstract : Supplemental Digital Content is Available in the Text.